DeyPoS: Deduplicatable Dynamic Proof of Storage for Multi-User Environment (International Journal of Engineering and Computer Science, 2017)
DeyPos is a useful cryptographic primitive that permits a user to check the integrity and systematically update the files in a cloud server. There has been many solutions proposed for Dynamic Proof of Storage in singleuser environment but for multi user problems is still unsolvable. A multi-user cloud storage system needs the secure client side cross user deduplication technique, which allows a user to stop the uploading process and gain the ownership of the files immediately, when other owners of the same files have uploaded them to the cloud server.As we know, none of the existing dynamic PoSs can support this technique. In this paper, we elaborate the concept of deduplicatable dynamic proof of storage and propose an efficient construction called DeyPoS, to achieve dynamic Proof of Storage and secure cross-user deduplication, simultaneously.To build a novel tool called Homomorphic Authenticated Tree (HAT) to address challenges such as structure diversity and private tag generation.Hence we prove the security of our construction, and the theoretical analysis and experimental results show that our research is practically valid and applicable.